2020
DOI: 10.3390/ani10122418
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Salmonella spp. Isolates from Swine: Virulence and Antimicrobial Resistance

Abstract: Salmonella is one of the most important zoonotic pathogens worldwide. Swine represent typical reservoirs of this bacterium and a frequent source of human infection. Some intrinsic traits make some serovars or strains more virulent than others. Twenty-nine Salmonella spp. isolated from pigs belonging to 16 different serovars were analyzed for gastric acid environment resistance, presence of virulence genes (mgtC, rhuM, pipB, sopB, spvRBC, gipA, sodCI, sopE), antimicrobial resistance and presence of antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
4
11
0
Order By: Relevance
“…In wild birds, where genomic investigations are becoming increasingly common, Enterobacteriales containing resistance genes to high-priority antimicrobials (e.g., bla CTX-M-65 , bla IMP-4 , mcr-1 ), and international clones have been identified [ 8 , 43 45 ]. The resistance identified in raccoons and other sources on swine farms in our study mirrors that found in swine in other parts of the world (e.g., sulfonamides, aminoglycosides, tetracyclines) [ 46 48 ]. Our findings of widespread tetracycline resistance genes ( tetA , tetB ) that were not associated with particular sources, locations, or years are plausibly driven by the swine farm environment, since tetracyclines, among other antimicrobials, are among the more commonly used antimicrobials in the Canadian swine industry [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 75%
“…In wild birds, where genomic investigations are becoming increasingly common, Enterobacteriales containing resistance genes to high-priority antimicrobials (e.g., bla CTX-M-65 , bla IMP-4 , mcr-1 ), and international clones have been identified [ 8 , 43 45 ]. The resistance identified in raccoons and other sources on swine farms in our study mirrors that found in swine in other parts of the world (e.g., sulfonamides, aminoglycosides, tetracyclines) [ 46 48 ]. Our findings of widespread tetracycline resistance genes ( tetA , tetB ) that were not associated with particular sources, locations, or years are plausibly driven by the swine farm environment, since tetracyclines, among other antimicrobials, are among the more commonly used antimicrobials in the Canadian swine industry [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, the presence of tet genes was revealed in 14 phenotypically susceptible strains. This result could be explained by the fact that not only efflux pumps contribute to tetracycline resistance but also other mechanisms, as suggested in other reports [33]. Moreover, we can surmise that the tet genes (tets (A) and (B)) detected in 14 tetracycline-sensitive strains are not expressed in the experimental conditions used in this study.…”
Section: Discussionsupporting
confidence: 48%
“…Rubislaw. The genes sopE and sodCI, both carried by phages, are more often associated with serotypes Enteritidis and Typhimurium, respectively, and they are rarely detected in other serotypes [23,53,54]. The obtained results expand the bacterial hosts spectrum of these phages, and suggest a possible reservoir for bacteriophages harboring virulence genes among salmonellae circulating in wild animals.…”
Section: Discussionmentioning
confidence: 66%